2016
DOI: 10.2196/mhealth.5905
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Gatekeeper-Stakeholders in Development of a Mobile Health Intervention to Improve Medication Adherence Among African American and Pacific Islander Elderly Patients With Hypertension

Abstract: BackgroundApproximately 70 million people in the United States have hypertension. Although antihypertensive therapy can reduce the morbidity and mortality associated with hypertension, often patients do not take their medication as prescribed.ObjectiveThe goal of this study was to better understand issues affecting the acceptability and usability of mobile health technology (mHealth) to improve medication adherence for elderly African American and Native Hawaiian and Pacific Islander patients with hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Participants’ feedback also suggests that efficacious approaches should aim to strike a balance between the need for individualized and collective social support for more meaningful and beneficial user experiences. Similar themes advocating for personalization to the individual’s needs were identified by AA gatekeeper stakeholders involved in the development of an mHealth intervention for patients with hypertension [ 39 ]. Consistent with our participants, they emphasized the need to include churches in the launch of mHealth interventions.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Participants’ feedback also suggests that efficacious approaches should aim to strike a balance between the need for individualized and collective social support for more meaningful and beneficial user experiences. Similar themes advocating for personalization to the individual’s needs were identified by AA gatekeeper stakeholders involved in the development of an mHealth intervention for patients with hypertension [ 39 ]. Consistent with our participants, they emphasized the need to include churches in the launch of mHealth interventions.…”
Section: Discussionmentioning
confidence: 86%
“…As maintenance of a healthy religious/spiritual life is central to our prioritized audience [ 38 ], our connection of faith and healthy lifestyle through spiritual messaging and biblical scripture was harmonious. It has been previously shown that positive messaging through scripture may heighten the acceptability and use of mHealth interventions by AAs [ 39 ]. Our cultural tailoring strategies through both superficial (visual imagery of AAs) and deep (the Black Church) structures also likely increased the receptivity to adapting positive behavioral change strategies [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A research study carried out with hypertensive elderly people revealed an interest in receiving objective and simple phone messages that stimulated adhesion to the treatment. (6) Regarding this fact, it is important to emphasize that effective communication between client and professional is fundamental in health care. To achieve this, it is necessary to provide information in a language suitable for the educational and cultural level of the client.…”
Section: Sexualitymentioning
confidence: 99%
“…(4) Evidence points to the positive use of Short Message Service (SMS) to send text messages to boost health habits among clients with chronic conditions. (5)(6)(7)(8) With the expanded use of the Internet, smartphone apps such as WhatsApp Messenger have potentialized instant communication between client and professional regarding health communication, with a variety of resources of interaction, (9) increasing the possibilities of the use of text messages in health care.…”
Section: Introductionmentioning
confidence: 99%
“…Within mHealth technologies a handful of products have been developed within Indigenous or American Indian communities using community-based participatory research (CBPR) methodologies including breastfeeding, medication adherence, alcohol consumption during pregnancy, hypertension, and general healthy lifestyle support. 14 20 While these are notably important health priorities, none of these medical conditions are related to dementia and aging-in-place. The general exploration of mHealth or eHealth applications among adults supports the feasibility and indicates a general interest in technologies, though economic and connectivity limitations in rural and remote areas are always a strong concern.…”
Section: Introductionmentioning
confidence: 99%